Strategies to increase rural maternal utilization of skilled health personnel for childbirth delivery in low- and middle-income countries: a narrative review - Jeanette R. Nelson; Rebekah H. Ess; Ty T. Dickerson; Lisa H. Gren; L. Scott Benson; Stephen O. Manortey; Stephen C. Alder (Taylor & Francis Group, 2022)
Background Skilled attendance at birth is considered key to accomplishing Sustainable Development Goal (SDG) 3.1 aimed at reducing maternal mortality. Many maternal deaths can be prevented if a woman receives care by skilled health personnel. Maternal utilization of skilled health delivery services in rural areas in low- and middle-income countries is 70% compared to 90% in urban areas. Previous studies have found community-based interventions may increase rural maternal uptake of skilled health delivery services, but evidence is lacking on which strategies are most effective. Objective To review the effectiveness of community-based strategies to increase rural maternal utilization of skilled health personnel for childbirth delivery in low-and middle-income countries. Methods We conducted a narrative review. PubMed, CINAHL, Cochrane Library, and PsycINFO databases were searched for articles from database inception through 13 November 2019. Key search terms were pre-determined. Information was extracted on studies meeting our inclusion criteria: cluster and randomized trials, rural setting, reproductive aged women, community engagement, low- and middle-income countries. Studies were considered effective if statistically significant (p < 0.05). A narrative synthesis was conducted. Results Ten cluster randomized trials out of 5,895 candidate citations met the inclusion criteria. Strategies included home-based visits, women's groups, and combined approaches. Out of the ten articles, only three studies were found to significantly increase maternal uptake of skilled health personnel for delivery, and each used a different strategy. The results are inconclusive as to which strategies are most effective. Limitations of this review include heterogeneity and generalizability of studies. Conclusions This research suggests that different strategies may be effective at improving maternal utilization of skilled health personnel for delivery in certain rural settings while ineffective in others. More research is warranted to better understand the context in which strategies may be effective and under what conditions.